Multicolor Amplified Spontaneous Emissions Based on Organic Polymorphs That Undergo Excited‐State Intramolecular Proton Transfer. Issue 14 (24th February 2016) - Cheng, Xiao; Zhang, Yufei; Han, Shenghua; Li, Feng; Zhang, Hongyu; Wang, Yue
Abstract: Two polymorphs emitting near‐infrared (1 R form: α phase, λ em =702 nm, Φ f =0.41) and orange‐red fluorescence (1 O form: β phase, λ em =618 nm, Φ f =0.05) were synthesized by finely controlling the crystallization conditions of compound 1, a structurally simple excited‐state intramolecular proton transfer (ESIPT)‐active molecule. Multicolor amplified spontaneous emissions (ASEs) were realized, for the first time, based on these polymorphs. Notably, the 1 O crystal underwent heating‐induced phase transformation from the β phase to the α form in a single‐crystal to single‐crystal (SCSC) manner accompanied with an unprecedented ASE changing. The ASE behavior of polymorphs 1 R, 1 O as well as the ASE changing during SCSC was investigated. The feasibility of multicolor lasing based on the present organic polymorphs was confirmed, which may provide a new development strategy for organic laser science and technology. Abstract : Two organic polymorphs with near‐IR (1R: α‐phase) and orange‐red (1O: β‐phase) emissions were synthesized based on a structurally simple organic molecule that undergoes excited‐state intramolecular proton transfer. 1O can transform into the α phase accompanied with an unprecedented amplified spontaneous emmision changing in a single‐crystal to single‐crystal manner.